Enhancing the Retention of Healthcare Workers in Rural Areas: A Systematic Review (المجلة الدولية للبحوث العلمية, 2023)
Introduction: Rural areas globally face significant challenges in retaining healthcare workers, impacting the delivery of essential health services and exacerbating health disparities. This systematic review aimed to evaluate the effectiveness of various strategies implemented over the last 15 years to enhance healthcare worker retention in rural settings, with the goal of identifying evidence-based interventions that can inform policy and practice to improve rural healthcare delivery. Methods: The review focused exclusively on interventional studies and clinical trials published from 2007 to 2022. A comprehensive search of multiple databases, including PubMed, MEDLINE, Embase, CINAHL, and the Cochrane Library, was conducted using specific search terms related to healthcare worker retention in rural areas. Inclusion criteria targeted studies evaluating quantifiable outcomes of retention strategies, with exclusion criteria set to omit non-interventional studies, research focused on urban settings, and non-English publications. The study selection, data extraction, and quality assessment processes were rigorously conducted to ensure the reliability of the findings.Results: Twelve studies met the inclusion criteria, revealing a broad range of interventions from financial incentives and educational programs to supportive workplace interventions and community engagement strategies. Financial incentives demonstrated a notable positive impact on retention, with risk ratios ranging from 1.2 to 1.75, indicating a 20% to 75% increase in retention rates. Supportive workplace interventions also showed effectiveness, with a risk ratio of up to 1.4. However, the results for educational and community engagement strategies were more variable, suggesting the need for tailored approaches.Conclusions:  The review highlights the effectiveness of targeted interventions in enhancing the retention of healthcare workers in rural areas, particularly financial incentives and supportive workplace interventions. These findings underscore the importance of implementing multifaceted, evidence-based strategies tailored to the unique challenges of rural healthcare settings to improve workforce stability and healthcare delivery.